SYNDROME OF INCREASED EPITHELIAL PERMEABILITY IN PATIENTS WITH RHEUMATOID ARTHRITIS - Marufhanov H.M., Sibirkina M.V., Eshmurzayeva A. A (Galaxy International Interdisciplinary Research Journal, 2023)
Currently, the role of the syndrome of increased epithelial permeability of the mucous membrane of the gastrointestinal tract, primarily the intestine, as the main pathogenetic mechanism for the development of inflammatory diseases not only of the intestine, but also of other organs and systems, including rheumatological diseases, is being discussed. The integrity of the intestinal barrier was assessed using morphological examination of mucosal biopsies (CO) of various gastrointestinal tract sections, followed by staining with hematoxylin and eosin. Electron microscopy can be used to visualize the distances between epithelial cells and the width of intercellular spaces. he analysis of the conducted studies revealed significant morphological shifts in all the studied departments of the digestive tract in rheumatological diseases, which are expressed in an increase in infiltration of the stroma of intestinal villi by lymphocytes and plasma cells, expansion of microvessels, an increase in the number of interepithelial lymphocytes, an increase in intercellular gaps, loss of enterocytes connection with the basal with the basal membrane, which indicates the development of SPEP in this category of patients.